ANALISIS PARAMETER STABILITAS KAPAL UNTUK MENINGKATKAN OPERASIONAL PENANGKAPAN KAPAL PUKAT CINCIN DI PERAIRAN LAUT BANDA - Obed Metekohy (Fakultas Teknik Universitas Pattimura, 2021)
The fishing operation of ring trawlers in Banda Sea waters is a promising potential with abundant fish stocks. However, fishing ground conditions with extreme weather greatly affect fishing operations because they are not supported by adequate fishing facilities. In general, ring trawlers are made in a traditional way, with hereditary experience. The shipbuilding greatly affects the operational characteristics of fishing, especially when setting fishing gear, pulling nets with catches from the sea, and when ships departing to and returning from the fishing grounds. This study aims to analyze the stability parameters of the ship so that it can improve fishing operations and ensure the safety of fishermen. The method used in this research is descriptive method. Analysis of the stability parameters refers to the design regulations of the Fish vessel. The results showed that the characteristic parameters of the ratio of the width and height of the deck (L/B) were 93%, GM 62.23%, TR 35.55% less than the technical design standards so that it greatly affected the stability of the ship during fishing operations.